Light-Dependent Regulation of Cyanobacterial Phytochrome Expression - García-Domínguez, M. (American Society for Microbiology, 2000)
A histidine kinase protein (Cph1) with sequence homology and spectral characteristics very similar to those of the plant phytochrome has been recently identified in the cyanobacterium Synechocystis sp. strain PCC 6803. Cph1 together with Rcp1 (a protein homologue to the response regulator CheY) forms a light-regulated two-component system whose function is presently unknown. Levels of cph1 rcp1 mRNA increase in the dark and decrease upon reillumination. A dark-mediated increase in cph1 rcp1 mRNA levels was inhibited by the presence of glucose, but not by inhibition of the photosynthetic electron flow. The half-life of cph1 rcp1 transcript in the light was about fourfold shorter than in the dark, indicating that control of cph1 rcp1 transcript stability is one of the mechanisms by which light regulates expression of the cyanobacterial phytochrome. After 15 min of darkness, 3-min pulses of red, blue, green, and far-red light were equally efficient in decreasing the cph1 rcp1 mRNA levels. Red light downregulation was not reversed by far-red light, suggesting that cph1 rcp1 mRNA levels are not controlled by a phytochrome-like photoreceptor. Furthermore, a Synechocystis strain containing an H538R Cph1 point mutation, unable to phosphorylate Rcp1, shows normal light-dark regulation of the cph1 rcp1 transcript levels. Our data suggest a role of cyanobacterial phytochrome in the control of processes required for adaptation in light-dark and dark-light transitions.